2016
DOI: 10.1002/humu.23141
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Bioinformatics Prediction, Molecular Modeling, and Functional Analyses ofFOXC1Mutations in Patients with Axenfeld-Rieger Syndrome

Abstract: Mutations in the forkhead box C1 gene (FOXC1) cause Axenfeld-Rieger syndrome (ARS). Here, we investigated the effect of four ARS missense variants on FOXC1 structure and function, and examined the predictive value of four in silico programs for all 31 FOXC1 missense variants identified to date. Molecular modeling of the FOXC1 forkhead domain predicts that c.402G> A (p.C135Y) alters FOXC1's structure. In contrast, c.378A> G (p.H128R) and c.481A> G (p.M161V) are not predicted to change FOXC1's structure. Functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 45 publications
(55 reference statements)
2
20
0
Order By: Relevance
“…Therefore, there is no apparent correlation between the functional impairment caused by the missense mutation of FOXC1 and the severity of the phenotype. The phenotype of ARS varies considerably among cases, and even between the two eyes of the same patient (14,19,20). This is consistent with the presentation of the Chinese ARS patients of the present study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, there is no apparent correlation between the functional impairment caused by the missense mutation of FOXC1 and the severity of the phenotype. The phenotype of ARS varies considerably among cases, and even between the two eyes of the same patient (14,19,20). This is consistent with the presentation of the Chinese ARS patients of the present study.…”
Section: Discussionsupporting
confidence: 91%
“…To the best of our knowledge, 54 different genetic mutations of FOXC1 have been detected in ARS patients, including missense mutations (n=31), InDels/duplications (n=17) and nonsense mutations (n=6) (9). Most missense mutations affect the amino acids within the FHD, which impair the FOXC1 protein function by altering the protein structure, nuclear localization, transactivation activity, DNA-binding ability and protein stability (16,19). The deletions and duplications of FOXC1 induce ARS by affecting the FOXC1 protein level required for the normal development of ocular tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 31 missense mutations in FOXC1 , 22 have been molecularly investigated. Twenty nine of the 31 missense mutations affect amino‐acid residues within the FHD . These mutations impair FOXC1 function through different mechanisms by alteration of FOXC1 structure, nuclear localization, DNA‐binding capacity, transactivation activity, DNA‐binding specificity, and protein stability .…”
Section: The Genetic Basis Of Arsmentioning
confidence: 99%
“…Recently, a combination of functional analysis and bioinformatics algorithms were applied to ARS‐associated mutations to identify rapid and efficient bioinformatics tools for clinical diagnostic lab researchers to prioritize predicted deleterious mutations for further experimental characterization. The results showed that in the absence of functional data, PMUT, Provean, MutPred, I‐mutant3.0 and molecular modeling are all reliable means of predicting the pathogenicity of missense substitutions within the FOXC1 FHD and PITX2 HD (under review). See Figure for a diagnostic strategy for ARS.…”
Section: Diagnostic Approachmentioning
confidence: 99%
“…Aside from nuclear translocation, mutations within the FHD of FOXC1 can impair binding activity of FOXC1 to its target genes. Specifically, the R127H and S131L mutations in α-helix3 reduced FOXC1 binding to DNA by 90 % compared to wild-type FOXC1 binding efficiency [ 33 , 37 , 42 ]. Moreover, some mutations in the FHD were reported to cause other molecular defects to FOXC1.…”
Section: Foxc1: Background Function Structure and Mutationsmentioning
confidence: 99%